Rent Control and Unemployment Duration - Michael Svarer; Michael Rosholm; Jakob Roland Munch (Institute for the Study of Labor (IZA), 2003)
In this paper we investigate whether rent control affects the functioning of the labour market. Particularly, we focus on the effect of rent control on the length of individual unemployment duration. Theoretically, the effect is ambiguous. Rent control reduces housing mobility and could very well spill-over to mobility in the labour market. On the other hand to maintain their rent control benefits unemployed individuals are presumably less demanding when accepting a job in the local labour market. Based on a rich Danish data set we investigate the empirical contents of the issue, and find results that are in clear accordance with the theoretical predictions.
Keywords: J64; J61; C41; L51; D45; 330; rent control; unemployment duration; search model; Arbeitslosigkeit; Dauer; Mietpreisbindung; Arbeitsuche; Arbeitsmobilität; Schätzung; Dänemark